Steel sheet and method for manufacturing the same
Patent Information
- Application Number
- CN202580020831.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-01
- Filing Date
- 2025-03-05
- Publication Date
- 2026-10-16
AI Technical Summary
根据本发明,能够提供高强度且弯曲部的耐氢脆特性优异的钢板及其制造方法。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to steel plates and methods for manufacturing the same. Background Technology
[0002] In recent years, from the perspective of limiting greenhouse gas emissions in response to global warming, there is a demand to improve the fuel efficiency of automobiles. In order to ensure the lightweighting of the vehicle body and collision safety, the application of high-strength steel plates is gradually expanding.
[0003] In high-strength steel sheets, hydrogen embrittlement (also known as delayed fracture) can sometimes become a problem. Hydrogen embrittlement refers to the sudden fracture of steel components subjected to high stress under service conditions due to hydrogen intrusion from the environment. Generally, it is known that the higher the strength of the steel sheet, the more prone it is to hydrogen embrittlement. This is believed to be because the higher the tensile strength of the steel sheet, the greater the stress remaining in the steel sheet after component forming. The sensitivity to hydrogen embrittlement is referred to as hydrogen embrittlement resistance.
[0004] To date, various attempts have been made to improve the hydrogen embrittlement resistance of steel plates.
[0005] For example, Patent Document 1 describes a zinc-plated steel sheet characterized by having a specified chemical composition, wherein the steel microstructure, within a thickness range of 1 / 8 to 3 / 8 of the thickness centered at 1 / 4 of the thickness from the surface of the steel sheet, contains, by volume percent, 0-10% ferrite, 0-20% bainite, 70% or more tempered martensite, 0-10% primary martensite, 0-10% retained austenite, and 0-5% pearlite; after removing the zinc-plated coating, the amount of hydrogen released when the steel sheet is heated from room temperature to 200°C is less than 0.40 ppm relative to the mass of the steel sheet, the tensile strength is 1470 MPa or more, and no cracks are generated in a U-bending test with a stress equivalent to 1000 MPa for 24 hours. In addition, in Patent Document 1, the hydrogen that affects hydrogen embrittlement is the hydrogen released when the steel plate is heated at a relatively low temperature. In connection with this, in order to prevent hydrogen embrittlement cracking, it is taught that the amount of hydrogen released when the steel plate is heated from room temperature to 200°C should be limited to less than 0.40 ppm.
[0006] Patent Document 2 describes a high-strength cold-rolled steel sheet, characterized by having a specified chemical composition. At a position 1 / 4 of the sheet thickness from the surface, the microstructure comprises, by volume fraction, more than 70.0% tempered martensite, more than 3.0% and less than 10.0% retained austenite, a total of less than 25.0% ferrite and bainite, and less than 5.0% martensite. At a position 25 μm from the surface, the microstructure comprises, by volume fraction, more than 70% ferrite and bainite, and a total of less than 30% martensite and tempered martensite. At the position 25 μm from the surface, the average grain size of the martensite and the tempered martensite is less than 5.0 μm. The tensile strength is more than 1310 MPa, the uniform elongation is more than 5.0%, and the ratio of the ultimate bending radius R to the sheet thickness t at a 90°V bend, R / t, is less than 5.0. Furthermore, Patent Document 2 teaches that when the combined volume fraction of ferrite and bainite is 70% or more and the combined volume fraction of martensite and tempered martensite is 30% or less at a position 25 μm away from the surface of the steel plate in the thickness direction, and the average grain size of the martensite and tempered martensite is 5.0 μm or less, the surface of the steel plate is soft, the hard phase in the surface layer that serves as the initiation point of cracks is reduced and finely homogenized, thereby reducing the number of crack initiation points and suppressing hydrogen embrittlement.
[0007] Existing technical documents Patent documents Patent Document 1: International Publication No. 2019 / 212047 Patent Document 2: International Publication No. 2019 / 181950 Summary of the Invention
[0008] The problem that the invention aims to solve As mentioned above, it is known that the higher the strength of the steel sheet, the more likely hydrogen embrittlement cracking will occur, for example, in the bending section (hereinafter also referred to as "bending section") which is subjected to large plastic strain.
[0009] Therefore, the object of the present invention is to provide a steel sheet with high strength and excellent resistance to hydrogen embrittlement in the bending section through a new configuration, and a method thereof for manufacturing the same.
[0010] Methods for solving problems To achieve the aforementioned objectives, the inventors specifically focused on the microstructure of steel plates. Specifically, they discovered that by optimizing the chemical composition of the steel plate and ensuring its microstructure is predominantly martensitic, it is possible to achieve high strength, for example, a tensile strength of 1470 MPa or higher, and to improve the steel plate's resistance to hydrogen embrittlement. Furthermore, they found that by reducing large and sharp recesses on the steel plate surface, stress concentration points that could become the initiation point for hydrogen embrittlement cracking can be reduced, and by reducing hydrogen trapping sites in the steel, even at high strengths of 1470 MPa or higher, the occurrence of hydrogen embrittlement cracking at bending points can be significantly suppressed, thus completing this invention.
[0011] The present invention, which achieves the above objectives, is described below.
[0012] (1) A steel plate, characterized in that it has the following chemical composition: (in mass%) C: 0.16~0.35% Si: 0.001~0.80% Mn: 1.00~3.50%, P: below 0.050% S: Below 0.0100% Al: 0.001~1.000% Ti: 0.001~0.100% B: 0.0005~0.0050% N: below 0.0100% O: Below 0.0100% Cr: 0~1.00% Mo: 0~1.00% Cu: 0~1.00%, Ni: 0~1.00% Co: 0~1.00%, W: 0~1.00% Ta: 0~1.000% Sn: 0~1.00% Sb: 0~0.50%, Nb: 0~0.200% V: 0~1.00% As: 0~0.100% Zn: 0~1.000%, Ca: 0~0.0100% Mg: 0~0.0100% Zr: 0~0.0100% Hf: 0~0.0100% Bi: 0~0.0100% REM: 0~0.0100%, and The remaining portion consists of Fe and impurities. The steel microstructure at a location 1 / 4 thickness from the surface contains, by area %: Martensite: over 70% The total amount of ferrite and bainite: 0~20%, and Residual austenite: 0~10%, The number density of recesses with a depth exceeding 2 μm and an apex angle of less than 45 degrees on the surface is less than 10.0 per mm, and When the hydrogen release is determined by immersion in an aqueous solution of 100 g / L ammonium thiocyanate at 25 °C for 48 hours, followed by heating from room temperature to 300 °C at a heating rate of 100 °C / h using a temperature desorption analysis method, the following equation (1) is satisfied. H 100-200 / H 20-300 <0.30(1) H 100-200 Hydrogen emission at 100~200℃ (mass ppm) H 20-300 Hydrogen emission at 20~300℃ (mass ppm).
[0013] (2) The steel plate according to (1) above is characterized in that, when the C concentration is measured from the surface of the steel plate along the depth direction using a high-frequency glow discharge emission spectroscopy device (GDS), the following formula (2) is satisfied.
[0014] [Mathematical Expression 1] C b C content (mass%) of steel plate C n C concentration (mass%) at the nth measurement point x n : Depth of the nth measurement point (μm) x n-1 : Depth of the (n-1)th measurement point (μm) l: n when the depth of the measurement point reaches 5μm or more m: n when the depth of the measurement point reaches 30μm or more. (3) The steel plate according to (1) or (2) above, characterized in that the steel structure at a position 1 / 4 thickness away from the surface contains, in area %: The total amount of ferrite and bainite: 2~20%, and Residual austenite: 1~10%.
[0015] (4) The steel plate according to any one of (1) to (3) above is characterized in that its tensile strength is 1470 MPa or more.
[0016] (5) The steel plate according to any one of (1) to (4) above is characterized in that it has a hot-dip galvanized layer or an alloyed hot-dip galvanized layer on at least one surface.
[0017] (6) A component, characterized in that it comprises the steel plate described in any one of (1) to (5) above.
[0018] (7) The method for manufacturing the steel plate according to any one of (1) to (6) above, characterized in that it includes the following steps: (A) A hot rolling process comprising hot rolling a slab having the chemical composition described in (1) above, followed by coiling and cooling the resulting hot-rolled steel sheet, and satisfying the following conditions (A1) and (A2): (A1) When the steel plate temperature is above 1000℃, the cumulative reduction rate between oxide scale and steel scale is less than 50%, and (A2) The winding temperature is above 400°C and below 650°C and the above cooling satisfies the following formulas (3) to (5). [Mathematical Expression 2] in, [Mathematical Expression 3] [Mathematical Expression 4] T(t): The temperature of the steel plate [K] after t seconds following winding. tf: Time in seconds for the steel plate to reach a temperature of 673K. Nx: The total atomic fractions of Si, Mn, and Al in steel. Δt: The measurement interval of T(t) [seconds]; (B) A pickling process, comprising a pickling treatment lasting 30 to 200 seconds, wherein the hot-rolled steel sheet is subjected to a pickling process at an average speed of 10 m / min or higher in an environment containing 1.0 to 5.0 mol / L HCl and less than 0.10 mol / L Fe. 3+ It passes through an aqueous solution with a temperature of 70~90℃; (C) Cold rolling process, in which the pickled hot-rolled steel sheet is cold rolled with a reduction rate of 30-75%; (D) A first heat treatment process, which includes heating the obtained cold-rolled steel sheet to a maximum heating temperature of Ac3~950°C, followed by cooling to below 40°C, and satisfying the following conditions (D1) and (D2): (D1) After reaching the aforementioned maximum heating temperature, the dwell time at 600~700℃ is less than 50 seconds, the dwell time at 450~600℃ is less than 500 seconds, and the dwell time at Ms~450℃ is less than 100 seconds. (D2) The average cooling rate between 200℃ and Ms is above 20℃ / second; (E) A second heat treatment process, which includes heating the cold-rolled steel sheet after the first heat treatment to a maximum heating temperature of 80~300°C, and satisfying the following formulas (6) and (7).
[0019] [Mathematical Expression 5] in, [Mathematical Expression 6] t: Time elapsed after reaching 80℃ [seconds] tf: End time of residence at 80~300℃ [seconds] T: Temperature at time t [K] T max Maximum heating temperature [K] (8) The method according to (7) above is characterized in that, in the first heat treatment process above, the atmosphere between Ac1 and Ac3 when the cold-rolled steel sheet is heated to the highest heating temperature satisfies the following formula (8).
[0020] [Mathematical Expression 7] pH2O: Partial pressure of water vapor pH2: partial pressure of hydrogen Invention Effects According to the present invention, a steel plate with high strength and excellent resistance to hydrogen embrittlement at the bending section and a method thereof are provided. Attached Figure Description
[0021] Figure 1 This is a diagram illustrating a method for measuring the number density of recesses with a depth exceeding 2 μm and an apex angle of less than 45 degrees on the surface of a steel plate according to an embodiment of the present invention.
[0022] Figure 2 This diagram schematically illustrates a test method used to evaluate the hydrogen embrittlement resistance of bent sections. Detailed Implementation
[0023] <steel plate> The steel plate of the present invention is characterized in that it has the following chemical composition: (in mass%), C: 0.16~0.35% Si: 0.001~0.80% Mn: 1.00~3.50%, P: below 0.050% S: Below 0.0100% Al: 0.001~1.000% Ti: 0.001~0.100% B: 0.0005~0.0050% N: below 0.0100% O: Below 0.0100% Cr: 0~1.00% Mo: 0~1.00% Cu: 0~1.00%, Ni: 0~1.00% Co: 0~1.00%, W: 0~1.00% Ta: 0~1.000% Sn: 0~1.00% Sb: 0~0.50%, Nb: 0~0.200% V: 0~1.00% As: 0~0.100% Zn: 0~1.000%, Ca: 0~0.0100% Mg: 0~0.0100% Zr: 0~0.0100% Hf: 0~0.0100% Bi: 0~0.0100% REM: 0~0.0100%, and The remaining portion consists of Fe and impurities. The steel microstructure at a location 1 / 4 thickness from the surface contains, by area %: Martensite: over 70% The total amount of ferrite and bainite: 0~20%, and Residual austenite: 0~10%, The number density of recesses with a depth exceeding 2 μm and an apex angle of less than 45 degrees on the surface is less than 10.0 per mm, and When the hydrogen release is determined by immersion in an aqueous solution of 100 g / L ammonium thiocyanate at 25 °C for 48 hours, followed by heating from room temperature to 300 °C at a heating rate of 100 °C / h using a temperature desorption analysis method, the following equation (1) is satisfied. H 100-200 / H 20-300 <0.30(1) H 100-200 Hydrogen emission at 100~200℃ (mass ppm) H 20-300 Hydrogen emission at 20~300℃ (mass ppm) As mentioned above, it is known that the higher the strength of the steel sheet, the more prone it is to hydrogen embrittlement. In particular, for steel sheets with very high strength, such as tensile strength of 1470 MPa or more, the steel microstructure typically contains martensite as the main component to ensure high strength. On the other hand, in the case of such high-strength steel sheets with martensite as the main component, hydrogen infiltrating the steel accumulates at the original austenite grain boundaries in the martensite microstructure, thereby reducing the bonding strength of the grain boundaries. These grain boundaries with reduced bonding strength can sometimes become the starting point for embrittlement, resulting in hydrogen embrittlement.
[0024] Therefore, the inventors first discovered that by optimizing the chemical composition of the steel sheet, particularly by including a specified amount of Ti and B in the steel, more specifically 0.001 to 0.100% by mass and 0.0005 to 0.0050% by mass respectively, it is possible to sufficiently ensure the solid solution of B, thereby improving hardenability and strengthening the original austenite grain boundaries. More specifically, by including Ti, N, which exists as an impurity in the steel, can be fixed as titanium nitride (TiN), thereby suppressing the consumption of solid solution B in the formation of boron nitride (BN). As a result, solid solution B can be sufficiently ensured in the steel. Here, solid solution B improves the hardenability of the steel sheet, facilitates the formation of a martensite-based steel structure, more specifically, facilitates the formation of a steel structure containing more than 70% martensite by area, and also helps to strengthen the original austenite grain boundaries, thereby improving the hydrogen embrittlement resistance of the steel sheet. Therefore, according to embodiments of the present invention, the steel plate, in particular, through a specific combination of a prescribed chemical composition of a steel plate containing Ti and B and a steel microstructure containing 70% or more martensite by area%, can achieve high strength of the steel plate, for example, a tensile strength of 1470 MPa or more, and improve the hydrogen embrittlement resistance of the steel plate.
[0025] Furthermore, as mentioned above, hydrogen embrittlement cracking is particularly prone to occur in bending sections subjected to large plastic strain. Therefore, the inventors conducted further research to improve the hydrogen embrittlement resistance of such bending sections. As a result, the inventors discovered that by reducing the relatively large and sharp recesses on the surface of the steel plate, and more specifically, by controlling the number density of recesses with a depth exceeding 2 μm and a apex angle of less than 45 degrees on the surface of the steel plate to less than 10.0 per mm, it is possible to reduce stress concentration points that may become the initiation point of hydrogen embrittlement cracking in the bending section, thereby improving the hydrogen embrittlement resistance of the bending section.
[0026] Figure 1 This is a diagram illustrating a method for measuring the number density of recesses with a depth exceeding 2 μm and a apex angle of 45 degrees or less on the surface of a steel plate according to an embodiment of the present invention. Specifically, refer to... Figure 1 (c) The steel plate 1 has a recess 2 on its surface, in which the distance (depth) D from the center line CL to the deepest position A, calculated by least squares method according to the profile of the surface height SH, exceeds 2 μm. Furthermore, in the recess 2, a vertex angle θ is formed by the line segment connecting the position A and the intersection points B and C of the center line CL with the recess 2. If the vertex angle θ is less than 45 degrees, such a large and sharp recess 2 may become a stress concentration point, and is therefore considered to be prone to becoming the starting point of hydrogen embrittlement cracking in the bending section. Therefore, the inventors have found that, as will be described in detail later in relation to the manufacturing method, particularly by properly controlling the hot rolling and pickling processes, the surface unevenness of the steel plate can be sufficiently reduced; more specifically, the number density of recesses with a depth exceeding 2 μm and a vertex angle of less than 45 degrees in the surface can be controlled to less than 10.0 per mm. As a result, the steel plate according to the embodiment of the present invention has a sufficiently reduced number of stress concentration points that can become the starting point of hydrogen embrittlement cracking, thus improving the hydrogen embrittlement resistance in the bending section. The method for determining the number density of the concave portion will be explained in more detail later.
[0027] On the other hand, according to the inventors' research, simply reducing the relatively large and sharp recesses on the surface of the steel sheet is sometimes insufficient to adequately improve the hydrogen embrittlement resistance of the bent portion. Therefore, the inventors conducted further research focusing on the steel microstructure of the steel sheet. As a result, the inventors discovered that, as will be described in detail later in relation to the manufacturing method, by appropriately heat-treating the cold-rolled steel sheet, it is possible to reduce the hydrogen trapping sites in the steel. Through this reduction of hydrogen trapping sites and the specific combination of controlling the number density of recesses on the surface of the steel sheet as described above, the hydrogen embrittlement resistance of the bent portion can be significantly improved.
[0028] To explain in more detail, the steel sheet of the embodiments of the present invention is predominantly martensite, but martensite is generally known to be a hard structure with high dislocation density. Dislocations have the property of trapping hydrogen intruding into the steel, so hydrogen tends to accumulate in steel sheets with a predominantly martensite structure, making it very difficult to improve hydrogen embrittlement resistance. In response, the inventors have discovered that by heat-treating the cold-rolled steel sheet under appropriate conditions, such hydrogen trapping sites associated with dislocations can be significantly reduced. While not intended to be bound by any particular theory, it can be considered that by heat-treating the cold-rolled steel sheet under appropriate conditions, sufficient dissolved carbon (C) can be ensured in the steel, causing this dissolved C to be fixed to dislocations before hydrogen. As a result, it is believed that the function of dislocations as hydrogen trapping sites in the steel can be significantly reduced or suppressed. Regarding the reduction of hydrogen capture sites in such steel, the inventors have discovered that by immersing a steel plate in an aqueous solution of ammonium thiocyanate at a concentration of 100 g / L at 25°C for 48 hours, and then heating it from room temperature to 300°C at a heating rate of 100°C / h using a temperature desorption analysis method, and measuring the amount of hydrogen released, a steel structure satisfying the following formula (1) can be formed.
[0029] H 100-200 / H 20-300 <0.30(1) H 100-200 Hydrogen emission at 100~200℃ (mass ppm) H 20-300 Hydrogen emission at 20~300℃ (mass ppm) If we explain equation (1) in more detail, it is known from the inventors' experiments that hydrogen trapped by dislocations is released in the temperature range of 100~200°C when subjected to temperature-induced desorption analysis under the above conditions. Therefore, it can be understood that H in equation (1) is... 100-200 / H 20-300 The smaller the value, more specifically, the smaller the proportion of hydrogen released (mass ppm) at 100~200℃ to the total hydrogen released (mass ppm) at 20~300℃, the less hydrogen is trapped by dislocations in the steel. The steel sheet of the embodiments of the present invention is predominantly martensite, therefore the number of dislocations is relatively large. Nevertheless, H 100-200 / H 20-300 The fact that the value is small can also be said to confirm that the number of hydrogen trapping sites associated with dislocations in steel is reduced by the solid solution of C and the fixation of dislocations in steel.
[0030] The inventors conducted further research from this perspective and found that by reducing the hydrogen capture sites in steel to the H in the above formula (1), 100-200 / H 20-300With a value below 0.30, and through a specific combination with the control of the number density of recesses in the steel sheet surface as previously described, the hydrogen embrittlement resistance of the bending portion can be significantly improved. Therefore, the steel sheet according to an embodiment of the present invention achieves high strength, more specifically, a strength of 1470 MPa or higher, through a martensitic steel structure, while also significantly improving the hydrogen embrittlement resistance of the bending portion. Therefore, the steel sheet according to the embodiment of the present invention is particularly useful in the automotive field where a high level of strength and hydrogen embrittlement resistance are required.
[0031] The steel plate according to the embodiments of the present invention will now be described in more detail. Furthermore, in the following description, unless otherwise specified, the unit "%" for the content of each element refers to "mass%". Moreover, in this specification, the "~" indicating a numerical range is used to mean the lower and upper limits of the values described before and after it, unless otherwise specified.
[0032] [C: 0.16~0.35%] Carbon (C) is an essential element for ensuring the strength of steel plates. To achieve this effect, the C content is set at 0.16% or more. The C content can be 0.18% or more, 0.20% or more, 0.22% or more, or 0.24% or more. On the other hand, if the C content is excessive, the hydrogen embrittlement resistance and uniform elongation at the bend may decrease due to the excessive increase in strength. Therefore, the C content is set at 0.35% or less. The C content can be 0.32% or less, 0.30% or less, 0.28% or less, or 0.26% or less.
[0033] [Si: 0.001~0.80%] Silicon (Si) is an element that inhibits the formation of iron carbides and helps improve strength and formability. To fully obtain these effects, the Si content is set to 0.001% or more. The Si content can be 0.01% or more, 0.05% or more, 0.10% or more, 0.20% or more, 0.30% or more, or 0.40% or more. On the other hand, if the Si content is excessive, local ductility may decrease, and the resistance to hydrogen embrittlement in the bending section may decrease. Therefore, the Si content is set to 0.80% or less. The Si content can be 0.70% or less, 0.60% or less, or 0.50% or less.
[0034] [Mn: 1.00~3.50%] Manganese (Mn) is a strong austenite stabilizing element and is effective in increasing the strength of steel plates. To achieve this effect, the Mn content is set at 1.00% or more. The Mn content can be 1.20% or more, 1.50% or more, 1.80% or more, 2.00% or more, 2.20% or more, or 2.40% or more. On the other hand, excessive Mn content leads to excessive martensite formation, sometimes reducing hydrogen embrittlement resistance and / or uniform elongation. Therefore, the Mn content is set at 3.50% or less. The Mn content can be 3.40% or less, 3.20% or less, 3.00% or less, 2.80% or less, 2.60% or less, or 2.50% or less.
[0035] [P: below 0.050%] Phosphorus (P) is a solid solution strengthening element and is effective in increasing the strength of steel plates. However, excessive addition can sometimes degrade weldability and toughness. Therefore, the P content is set to 0.050% or less. The preferred P content is 0.045%, 0.035%, or 0.020% or less. The P content can be 0%, but drastically reducing the P content increases the cost of P removal. Therefore, from an economic point of view, the P content can be 0.0001% or more, 0.0005% or more, or 0.001% or more.
[0036] [S: below 0.0100%] Sulfur (S) is an element present as an impurity, sometimes forming MnS in steel, which deteriorates toughness and porosity. Therefore, the S content is set to be 0.0100% or less. The preferred S content is 0.0050%, 0.0040%, or 0.0030% or less. The S content can be 0%, but to drastically reduce the S content, desulfurization costs increase. Therefore, from an economic point of view, the S content can be 0.0001% or more, 0.0003% or more, or 0.0005% or more.
[0037] [Al: 0.001~1.000%] Al (aluminum) is an element that functions as a deoxidizer. To achieve this effect, the Al content is set at 0.001% or more. The Al content can be 0.010% or more, 0.020% or more, 0.030% or more, 0.040% or more, or 0.050% or more. On the other hand, even with excessive Al content, the effect saturates, and exceeding the necessary content in the steel sheet leads to increased manufacturing costs. Furthermore, excessive Al content raises the phase transformation temperature of the steel, increasing the load during hot rolling, which can sometimes result in a decrease in the mechanical properties of the steel sheet. Therefore, the Al content is set at 1.000% or less. The Al content can be 0.800% or less, 0.600% or less, 0.300% or less, or 0.100% or less.
[0038] [Ti: 0.001~0.100%] Titanium (Ti) is an effective element for fixing nitrogen (N) present as an impurity in steel as TiN and for suppressing the precipitation of boron (B) as nitride (BN). To achieve this effect, the Ti content is set to 0.001% or more. The Ti content can be 0.005% or more, 0.010% or more, 0.015% or more, or 0.020% or more. On the other hand, even with excessive Ti content, the effect saturates, and exceeding the necessary amount in the steel sheet leads to an increase in manufacturing costs. Therefore, the Ti content is set to 0.100% or less. The Ti content can be 0.090% or less, 0.080% or less, 0.060% or less, or 0.040% or less.
[0039] [B: 0.0005~0.0050%] Boron (B) is an element that improves hardenability and thus contributes to increased strength. Furthermore, B is effective in strengthening the original austenite grain boundaries through segregation, thereby improving resistance to hydrogen embrittlement. To fully achieve these effects, the B content is set to 0.0005% or more. The B content can be 0.0008% or more, 0.0010% or more, 0.0012% or more, 0.0015% or more, 0.0018% or more, 0.0020% or more, or 0.0022% or more. On the other hand, excessive B content can sometimes lead to excessive formation of borides in the steel, reducing the hardenability of the steel sheet. Therefore, the B content is set to 0.0050% or less. The B content can be 0.0045% or less, 0.0040% or less, 0.0035% or less, 0.0030% or less, or 0.0028% or less.
[0040] [N: below 0.0100%] Nitrogen (N) is an element present as an impurity. High N content can sometimes form large nitrides in steel, reducing its flexibility and porosity. Therefore, the N content is set to be below 0.0100%. Preferably, the N content is below 0.0080%, 0.0060%, or 0.0050%. The N content can be 0%, but to drastically reduce the N content, the cost of nitrogen removal becomes high. Therefore, from an economic point of view, the N content can be above 0.0001%, 0.0003%, or 0.0005%.
[0041] [O: below 0.0100%] Oxygen (O) is an element present as an impurity. High O content can sometimes form large oxides in steel, reducing its flexibility and porosity. Therefore, the O content is set to 0.0100% or less. Preferably, the O content is 0.0080%, 0.0060%, or 0.0050% or less. While the O content can be 0%, drastically reducing it increases manufacturing costs. Therefore, from a manufacturing cost perspective, the O content can be 0.0001% or more, 0.0003% or more, or 0.0005% or more.
[0042] The basic chemical composition of the steel plate according to embodiments of the present invention is as described above. Furthermore, the steel plate may, as needed, contain at least one of the following elements to replace a portion of the remaining Fe.
[0043] [Cr: 0~1.00%, Mo: 0~1.00%, Cu: 0~1.00%, Ni: 0~1.00%, Co: 0~1.00%, W: 0~1.00%, Ta: 0~1.000%, Sn: 0~1.00%, Sb: 0~0.50%, Nb: 0~0.200% and V: 0~1.00%] Cr (chromium), Mo (molybdenum), Cu (copper), Ni (nickel), Co (cobalt), W (tungsten), Ta (tantalum), Sn (tin), Sb (antimony), Nb (niobium), and V (vanadium) are all effective elements for increasing the strength of steel plates. The content of these elements can be 0%, but to achieve the desired effect, at least one of these elements can be included in the steel plate as needed. However, even with excessive content of these elements, the effect saturates, potentially leading to increased manufacturing costs. Therefore, the contents of Cr, Mo, Cu, Ni, Co, W, Sn, and V are set to 1.00% or less, and can be 0.60%, 0.50%, 0.30%, or 0.20% or less, respectively. Similarly, the Ta content is set to 1.000% or less, and can be 0.600%, 0.500%, 0.300%, or 0.200% or less. Likewise, the Sb content is set to 0.50% or less, and can be 0.30% or less, or 0.10% or less. Similarly, the Nb content is set to below 0.200%, but can be below 0.100% or below 0.060%. The lower limits for these elements, such as Cr, Mo, Cu, Ni, Co, W, Sn, Sb, and V, can be above 0.001% or above 0.01%. Similarly, the Ta and Nb contents can be above 0.001% or above 0.005%.
[0044] [As: 0~0.100%] Arsenic (As) is an effective element for improving corrosion resistance. While the As content can be 0%, to achieve this effect, the As content is preferably 0.001% or more, specifically 0.005% or more, or 0.010% or more. On the other hand, even with excessive As content, the effect saturates, and exceeding the necessary amount in the steel sheet leads to increased manufacturing costs. Therefore, the As content is set to 0.100% or less, specifically 0.050%, 0.030%, or 0.020% or less.
[0045] [Zn: 0~1.000%, Ca: 0~0.0100%, Mg: 0~0.0100%, Zr: 0~0.0100%, Hf: 0~0.0100%, Bi: 0~0.0100% and REM: 0~0.0100%] Zinc (Zn) is an effective element for controlling the shape of inclusions in steel. Calcium (Ca), magnesium (Mg), zirconium (Zr), hafnium (Hf), and rare earth elements (REMs) contribute to the fine dispersion of inclusions in steel. Bismuth (Bi) mitigates the microsegregation of substitutional alloying elements such as Mn and Si in steel. The content of these elements can be 0%, but since they each contribute to improved workability of the steel sheet, at least one of these elements can be included in the steel sheet as needed. However, even with excessive content of these elements, the effect saturates, potentially leading to increased manufacturing costs. Therefore, the Zn content is set to 1.000% or less, and can be 0.500%, 0.200%, 0.100%, or 0.050% or less. Similarly, the contents of Ca, Mg, Zr, Hf, Bi, and REMs are set to 0.0100% or less, and can be 0.0080%, 0.0060%, or 0.0030% or less. Regarding the lower limits for these elements, for example, the Zn content can be above 0.001% or above 0.005%. Similarly, the contents of Ca, Mg, Zr, Hf, Bi, and REM can also be above 0.0001% or above 0.0005%, respectively. In this specification, REM refers to the collective content of 17 elements: scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71, which are lanthanide elements. The REM content is the total content of these elements.
[0046] In the steel plate of the embodiment of the present invention, the remaining portion besides the aforementioned elements consists of Fe and impurities. Here, impurities refer to components that are mixed in during the industrial manufacturing of steel plates due to various reasons in the manufacturing process, such as raw materials like ore or scrap iron.
[0047] The chemical composition of the steel plate according to embodiments of the present invention can be determined by conventional analytical methods. For example, the chemical composition of the steel plate can be determined using inductively coupled plasma atomic emission spectrometry (ICP-AES). C and S can be determined using combustion-infrared absorption method, N can be determined using inactive gas melting-thermal conductivity method, and O can be determined using inactive gas melting-non-dispersive infrared absorption method.
[0048] [Steel Structure] [Martensite: 70% or more, ferrite and bainite combined: 0-20%, and retained austenite: 0-10%] In the steel plate of the embodiment of the present invention, the steel microstructure in the cross section at a position 1 / 4 thickness away from the surface of the steel plate contains, by area %: martensite: 70% or more, ferrite and bainite in total: 0 to 20%, and retained austenite: 0 to 10%.
[0049] In embodiments of the present invention, martensite includes quenched martensite (primary martensite) and tempered martensite. Martensite, being a high-dislocation-density and hard structure, contributes to increased strength. To obtain the desired high strength, the martensite area fraction is set to 70% or more. The martensite area fraction can be 75% or more, 80% or more, 85% or more, or 90% or more. There is no particular upper limit, so the martensite area fraction can be 100% or less, or less than 98%. However, from the viewpoint of improving uniform elongation, a lower martensite area fraction is preferred, for example, less than 97%, less than 95%, or less than 92%.
[0050] Ferrite, in particular, is a microstructure with excellent ductility, contributing to improved elongation. However, if the combined area ratio of ferrite and bainite is too high, the area ratio of martensite decreases, thus failing to achieve the desired strength. Therefore, the combined area ratio of ferrite and bainite is set to 20% or less. The combined area ratio of ferrite and bainite can be 18% or less, 15% or less, 12% or less, 10% or less, or 8% or less. The combined area ratio of ferrite and bainite can be 0%, but from the viewpoint of improving uniform elongation, it is preferable to be 1% or more or 2% or more, and it can also be 3% or more or 5% or more.
[0051] Retained austenite improves the ductility of steel sheets through the TRIP effect, which involves the transformation to martensite during processing-induced phase transformation. However, if the area ratio of retained austenite is too high, the area ratio of martensite decreases, thus failing to achieve the desired strength. Therefore, the area ratio of retained austenite is set to 10% or less. The area ratio of retained austenite can be 9% or less, 8% or less, 7% or less, 6% or less, or 5% or less. The area ratio of retained austenite can be 0%, but from the viewpoint of improving uniform elongation, it is preferable to be 1% or more or 2% or more, and it can also be 3% or more or 4% or more.
[0052] [Remaining tissue: Total 0-10%] The remaining microstructure other than martensite, ferrite, bainite, and retained austenite can be 0% in terms of area ratio. If remaining microstructure is present, it is pearlite. From the viewpoint of ensuring the aforementioned effects based on martensite, ferrite, bainite, and retained austenite, the total area ratio of the remaining microstructure is preferably 10% or less, for example, 8% or less, 6% or less, 4% or less, 3% or less, or 2% or less. On the other hand, the area ratio of the remaining microstructure can be 0.5% or more, or 1% or more.
[0053] [Identification of steel microstructure and calculation of area ratio] The identification of the steel microstructure and the calculation of its area ratio were performed using secondary electron imaging and X-ray diffraction using a FE-SEM (field emission scanning electron microscope, such as the JEOL JSM-7200F, measured at an accelerating voltage of 15 kV). First, samples were collected from a section perpendicular to the steel plate surface as the observation surface. This surface was mechanically ground to a mirror finish and then etched using a nitric acid-ethanol solution. Next, in one or more observation fields covering a thickness of 1 / 8 to 3 / 8 of the steel plate, centered at a point 1 / 4 of the thickness from the surface, a total area of 2.0 × 10⁻⁶ was determined. -9 m 2Secondary electron images were taken of the areas described above. Based on the obtained secondary electron images, the area ratios of the total martensite and retained austenite, pearlite (if present), and ferrite and bainite were measured. First, areas with high brightness and where the underlying structure was not revealed by corrosion were identified as primary martensite and retained austenite. Next, areas with multiple cementite precipitates exhibiting underlying structure but with different elongation directions were identified as tempered martensite. Next, areas where cementite precipitated in layers were identified as pearlite (the sum of pearlite and cementite). The remaining areas other than the above structures were identified as ferrite and bainite. For reference, areas with low brightness and where the underlying structure was not identified could be identified as ferrite, and areas that did not meet either of the above criteria could be identified as bainite. The area ratios of each structure thus identified were calculated using a point counting method. The area ratio of martensite can be obtained by subtracting the area ratio of retained austenite, as determined by the X-ray diffraction method described below, from the total area ratio of tempered martensite, primary martensite, and retained austenite.
[0054] The area ratio of retained austenite was determined by X-ray diffraction. Specifically, the austenite was removed from the surface of the steel plate along the thickness direction to a depth of 1 / 4 by mechanical and chemical grinding. Then, the microstructure ratio of retained austenite was calculated based on the integral intensity ratio of the diffraction peaks of the (200), (211) phase of the bcc phase and the (200), (220), (311) phase of the fcc phase obtained by using MoKα1 rays as characteristic X-rays on the ground sample, and this ratio was taken as the area ratio of retained austenite.
[0055] [Number density of recesses on the surface with a depth exceeding 2 μm and an apex angle of less than 45 degrees: less than 10.0 per mm] In the steel plate of the embodiment of the present invention, the number density of recesses with a depth exceeding 2 μm and a vertex angle of 45 degrees or less on the surface is controlled to be 10.0 recesses / mm or less. By controlling the number density of recesses with a depth exceeding 2 μm and a vertex angle of 45 degrees or less on the surface within such a range, as previously explained, stress concentration points that may become the starting point of hydrogen embrittlement cracking in the bending portion can be reduced, thereby improving the hydrogen embrittlement resistance of the bending portion. From the viewpoint of further improving the hydrogen embrittlement resistance of the bending portion, the lower the number density of these recesses, the more preferred it is, for example, it can be 8.0 recesses / mm or less, 6.0 recesses / mm or less, 5.0 recesses / mm or less, 4.0 recesses / mm or less, 3.0 recesses / mm or less, 2.0 recesses / mm or less, or 1.5 recesses / mm or less. The lower limit is not particularly limited and can be 0 recesses / mm. For example, the number density of recesses with a depth exceeding 2 μm and a vertex angle of 45 degrees or less on the surface can be 0.1 recesses / mm or more, 0.3 recesses / mm or more, or 0.5 recesses / mm or more.
[0056] [Method for determining the number density of recesses on a surface with a depth exceeding 2 μm and a vertex angle of less than 45 degrees] The number density of recesses with a depth exceeding 2 μm and a vertex angle of less than 45 degrees on the surface of the steel plate was determined as follows. First, a section perpendicular to the surface of the steel plate was used as the observation surface. Samples were collected, and the observation surface was mechanically ground to a mirror finish. Then, an FE-SEM (field emission scanning electron microscope, such as the JEOL JSM-7200F, with an accelerating voltage of 15 kV) was used to capture a reflected electron image of the steel plate surface (or the coating / steel plate interface if the steel plate has a coating) at 500x magnification. Figure 1 (a) The obtained reflected electron image is binarized to clarify the surface of the steel plate. Figure 1 (b)). In the reflected electron image, the coating is observed to be light-colored, while the substrate metal is dark-colored. However, during binarization, the threshold value is adjusted to distinguish between the light and dark areas. The converted binarized image is then converted into numerical data to obtain the surface height ( Figure 1 (c) The contour of SH). Image analysis software capable of performing this operation includes, for example, ImageJ. The centerline is obtained from the contour of the surface height using the least squares method. Figure 1 (c) CL), from the center line to the deepest position ( Figure 1 The distance from point A in (c) is ( Figure 1 In (c), the region exceeding 2 μm in D) is defined as a "recess with a depth exceeding 2 μm". The region is then defined by the deepest point connecting this recess (…). Figure 1 (c) A) and the intersection of the center line and the concave part ( Figure 1 The vertex angle formed by line segments B and C in (c) Figure 1In (c), the region where θ is less than 45 degrees is defined as "a recess in the surface with a depth exceeding 2 μm and a vertex angle less than 45 degrees". The same analysis is performed if the total measurement range (surface length) exceeds 1 mm. For example, if the surface length in one field of view is 200 μm, the above analysis is performed at least 5 times by changing the field of view. The total number of "recesses with a depth exceeding 2 μm and a vertex angle less than 45 degrees" obtained in each field of view is converted into a number density per 1 mm of surface length, and this is defined as the "number density of recesses in the surface with a depth exceeding 2 μm and a vertex angle less than 45 degrees". Here, surface length refers to the length along the contour of the surface height described above, which can be measured using image analysis software. As a means of measuring the contour of the surface height of a steel plate, a contact or laser roughness gauge is usually used. However, when the steel plate has a coating, it is first necessary to dissolve and peel off the coating using acid. However, in such a method, not only is the coating corroded during acid dissolution, but the substrate metal interface is also corroded simultaneously, raising concerns about changes from the original unevenness. Therefore, these methods are not recommended.
[0057] [H 100-200 / H 20-300 <0.30] In an embodiment of the present invention, the steel plate is immersed in an aqueous solution of ammonium thiocyanate at 100 g / L at 25°C for 48 hours, and then the amount of hydrogen released is measured by heating from room temperature to 300°C at a heating rate of 100°C / h using a temperature desorption analysis method, and the control is performed in a manner that satisfies the following formula (1).
[0058] H 100-200 / H 20-300 <0.30(1) H 100-200 Hydrogen emission at 100~200℃ (mass ppm) H 20-300 Hydrogen emission at 20~300℃ (mass ppm) The steel plate of the embodiment of the present invention is mainly composed of martensite. Here, martensite has a high dislocation density, and dislocations have the property of capturing hydrogen that has invaded the steel. As described above, when a temperature-induced desorption analysis is performed under the above conditions, the hydrogen captured by the dislocations is released in a temperature range of 100~200°C. Therefore, it can be understood that H in the above formula (1) 100-200 / H 20-300 The smaller the value, more specifically, the smaller the proportion of hydrogen released (mass ppm) at 100~200℃ to the total hydrogen released (mass ppm) at 20~300℃, the less hydrogen is trapped by dislocations in the steel. The steel sheet of the embodiments of the present invention is predominantly martensite, therefore the number of dislocations is relatively large. Nevertheless, in H...100-200 / H 20-300 When the value is small, it can be understood that dislocations in the steel are fixed by solid solution C, and the number of hydrogen trapping sites in the steel is reduced. According to the steel plate of the embodiment of the present invention, by reducing the number of hydrogen trapping sites in the steel to the value of H in the above formula (1), 100-200 / H 20-300 When the value is below 0.30, a specific combination with the previously described control of the number density of recesses in the steel plate surface can significantly improve the hydrogen embrittlement resistance of the bending section. From the viewpoint of further improving the hydrogen embrittlement resistance of the bending section, H... 100-200 / H 20-300 The smaller the value, the better; for example, it can be below 0.28, 0.25, 0.22, 0.20, or 0.18. There is no specific limitation on the lower limit; for example, H... 100-200 / H 20-300 The value can be greater than 0.01, greater than 0.05, or greater than 0.10.
[0059] [H 100-200 / H 20-300 [Determination] H 100-200 / H 20-300 The determination was performed as follows. First, in the case of unprocessed steel sheet, a test piece of approximately 25 mm × 10 mm was collected from a position other than the end in the width direction. In the case of plated steel sheet, the plating was dissolved using a 5% hydrochloric acid aqueous solution containing 0.04% by volume of an inhibitor (IBIT 710K manufactured by Asahi Chemical Industry Co., Ltd.) to remove the plating. Then, hydrogen was introduced into the test piece by immersion in a 100 g / L ammonium thiocyanate aqueous solution at 25°C for 48 hours. In the case of test pieces collected from processed parts, test pieces collected from flat parts that have never been directly processed or, even if processed, have been processed to a relatively low degree. The effects of the present invention can be achieved even if the processed part is unclear or even if the processed part satisfies the above formula (1). Next, the test piece containing hydrogen was heated from room temperature to 300°C at a heating rate of 100°C / h using a hydrogen determination system in steel (JTF-20A manufactured by J-SCIENCE LAB, Ltd.). The total amount of hydrogen released during the period up to 300°C was measured. 20-300 (mass ppm) and the amount of hydrogen released between 100°C and 200°C (H) 100-200 (mass ppm). Finally, H is determined by calculating their ratio. 100-200 / H 20-300 The value should be set to a room temperature range of 20~30℃.
[0060] [C concentration from the surface of the steel plate to depth based on GDS] In a preferred embodiment of the invention, the steel plate is controlled in such a manner that the C concentration is measured from the surface of the steel plate along the depth direction using a high-frequency glow discharge emission spectroscopy device (GDS) to satisfy the following formula (2).
[0061] [Mathematical Expression 8] C b C content (mass%) of steel plate C n C concentration (mass%) at the nth measurement point x n : Depth of the nth measurement point (μm) x n-1 : Depth of the (n-1)th measurement point (μm) l: n when the depth of the measurement point reaches 5μm or more m: n when the depth of the measurement point reaches 30μm or more. The left side of equation (2) above can be understood as an indicator of the degree of decarburization on the surface of the steel plate. More specifically, C... b This refers to the carbon content (mass%) of the steel plate. n This refers to the carbon concentration (mass%) at various measurement points using GDS (Gas Dioxide Dismutase) at depths ranging from 5 μm to 30 μm from the steel plate surface. Therefore, the greater the degree of decarburization, the higher the carbon concentration (mass%). b -C n The value of increases. Furthermore, the left side of equation (2) above represents C. b -C n The value (mass%) is obtained by multiplying the value by the distance (μm) between each measurement point and then adding the values. Therefore, the greater the degree of decarburization, the greater the value. On the other hand, the harder the steel plate surface, the easier it is for hydrogen embrittlement cracking to occur in the bending part. This tendency has become particularly significant with the progress of high strength steel plates. In this regard, in order to further improve the hydrogen embrittlement resistance of the bending part, the inventors have also conducted a detailed study on the control of the hardness of the surface part of the steel plate. As a result, the inventors found that, in addition to the specific combination of the reduction of hydrogen trapping sites and the control of the number density of the concave parts on the surface of the steel plate, the hydrogen embrittlement resistance of the bending part can be further significantly improved by decarburizing the surface part of the steel plate to a specified range, and more specifically, by controlling the C concentration in the depth direction of the surface part of the steel plate in a manner that satisfies the above formula (2).
[0062] From the viewpoint of further improving the resistance to hydrogen embrittlement in the bending section, a larger value on the left side of the above equation (2) is preferred. For example, it can be 2.2 or higher, 2.4 or higher, 2.6 or higher, 2.8 or higher, 3.0 or higher, or 3.2 or higher. There is no particular upper limit. For example, the value on the left side of the above equation (2) can be 6.0 or lower, 5.5 or lower, 5.0 or lower, 4.5 or lower, or 4.0 or lower.
[0063] [Method for determining the value on the left side of equation (2)] The value on the left side of the above equation (2) is determined using a high-frequency glow discharge emission spectrometer (GDS) as follows. In this embodiment, a high-frequency glow discharge emission spectrometer GD-Profiler2 manufactured by Horiba Manufacturing Co., Ltd. is used. First, the surface of the steel plate is made into an Ar atmosphere, and under the condition of generating glow plasma by applying voltage, the surface of the steel plate is sputtered while the analysis is performed in the depth direction. Then, based on the emission spectrum wavelength of the element-specific emission spectrum emitted by the atoms excited in the glow plasma, the elements contained in the steel plate are identified, and the luminescence intensity of the identified elements is estimated. Thus, the luminescence intensity distribution of the elements in each measurement time is obtained. The measurement interval is set to 0.1 seconds. Next, the sputtering velocity is determined by measuring the depth of the sputtering mark of the sample after GDS measurement, and the time is converted into depth. The depth of the sputtering mark can be measured by observing the surface using a commercially available microscope or laser microscope with height measurement function, or by cross-sectional observation. The sputtering depth that can be converted from sputtering time is defined as the depth from the surface of the steel plate. The obtained luminescence intensity is converted into mass by making a standard curve. The standard curve was constructed using a mechanically ground steel plate to a depth of 1 / 4 t and commercially available high-purity electrolytic iron. The C luminescence intensity of both was measured for 300 seconds at 0.1-second intervals, and the average C luminescence intensity over the 20-300 second period where the results were stable was calculated. The C concentration of the steel plate was known, and the C concentration of the high-purity electrolytic iron could be considered zero, thus obtaining a standard curve that could convert C luminescence intensity into C concentration (mass%). This yielded the measurement points (i.e., X points) for GDS measurements performed from a depth of 5 μm to 30 μm from the steel plate surface. n The C concentration (i.e., C) n ), based on these C concentrations and C b (i.e., the C content of the steel plate determined by the combustion-infrared absorption method), determine the value of the left side of the above formula (2). It should be noted that when the steel plate to be measured is a coated steel plate, the depth position where the luminescence intensity of Fe exceeds the luminescence intensity of the coating metal type (Zn if it is a zinc coated steel plate) is set to 0 μm.
[0064] [Plate thickness] The steel plate used in the embodiments of the present invention is not particularly limited, and typically has a plate thickness of 0.6 to 6.0 mm. For example, the plate thickness can be 1.0 mm or more, 1.2 mm or more, or 1.4 mm or more, and / or can be 5.0 mm or less, 4.0 mm or less, 3.0 mm or less, or 2.5 mm or less.
[0065] [Coating] The steel sheet in embodiments of the present invention can be a coated steel sheet having a coating on at least one surface, preferably on two surfaces. The coating is not particularly limited, and can be, for example, a hot-dip galvanized (GI), alloyed hot-dip galvanized (GA), or electro-galvanized (EG). These zinc coatings can have any composition known to those skilled in the art, and may contain additive elements such as Al and Mg in addition to Zn. Furthermore, the amount of coating applied is not particularly limited and can be a typical amount.
[0066] The steel sheet of the embodiments of the present invention achieves high strength, more specifically, a strength of 1470 MPa or higher, through a martensitic steel structure as described above. Furthermore, it achieves significantly improved resistance to hydrogen embrittlement in the bending portion. Therefore, the steel sheet of the embodiments of the present invention is particularly useful for use in components and the like in technical fields where high strength and resistance to hydrogen embrittlement are required at high levels, especially for use in automotive components. In a preferred embodiment, an automotive component comprising the steel sheet of the embodiments of the present invention is provided. Examples of automotive components include frame components such as front pillars, center pillars, side beams, and frame crossbeams, bumpers, and other structural components and reinforcing components requiring strength. These components only need to include the steel sheet of the embodiments of the present invention in at least a portion of them, thus satisfying the characteristics of the steel sheet described above in at least a portion of these components. In portions of the steel sheet that do not directly contact the die during forming processes such as stamping, or where the degree of processing in direct contact with the die is relatively low, the characteristics of the steel sheet do not change significantly before and after forming.
[0067] [Mechanical Properties] [Tensile strength (TS) and uniform elongation (uEL)] The steel sheet having the above-described chemical composition and steel structure achieves high tensile strength, specifically a tensile strength (TS) of 1470 MPa or more. The tensile strength is preferably 1500 MPa or more, 1550 MPa or more, or 1600 MPa or more. Despite having such very high tensile strength, the steel sheet according to the embodiment of the present invention, through the specific combination of the chemical composition and steel structure described above, can significantly suppress hydrogen embrittlement cracking at the bending portion. There is no particular upper limit to the tensile strength; for example, the tensile strength of the steel sheet can be 1800 MPa or less, 1750 MPa or less, or 1700 MPa or less. Furthermore, despite having such very high tensile strength, the steel sheet according to the embodiment of the present invention also achieves improved ductility. In particular, when the total area fraction of ferrite and bainite is 2% or more, and the area fraction of retained austenite is 1% or more, a uniform elongation (uEL) of 5.0% or more can be achieved. For example, the uniform elongation can be 5.2% or more, 5.5% or more, 5.8% or more, or 6.0% or more. There is no particular upper limit to the uniform elongation; for example, the uniform elongation of the steel plate can be less than 10.0% or less than 8.0%. Tensile strength and uniform elongation are determined by taking JIS 5 test pieces from a direction (C direction) preferably parallel to the rolling right angle of the steel plate along the length of the test piece, and performing tensile tests according to JIS Z 2241:2022. If the rolling direction of the steel plate cannot be determined, JIS 5 test pieces can be taken from any direction within the surface of the steel plate. If it is difficult to take JIS 5 test pieces, JIS 13B test pieces or small test pieces with a similar shape to JIS 13B test pieces can be used.
[0068] <Methods for manufacturing steel plates> Next, a preferred method for manufacturing the steel plate according to an embodiment of the present invention will be described. The following description is intended to illustrate a characteristic method for manufacturing the steel plate according to an embodiment of the present invention, and is not intended to limit the steel plate to a steel plate manufactured by the method described below.
[0069] The method for manufacturing the steel plate according to embodiments of the present invention includes the following steps: (A) A hot rolling process, which includes hot rolling a slab having the chemical composition described above in relation to a steel sheet, followed by coiling and cooling the resulting hot-rolled steel sheet, and satisfying the conditions (A1) and (A2) below. (A1) When the steel plate temperature is above 1000℃, the cumulative reduction rate between oxide scale and steel scale is less than 50%, and (A2) The winding temperature is above 400°C and below 650°C, and the above cooling satisfies the following formulas (3) to (5). [Mathematical Expression 9] in, [Mathematical Expression 10] [Mathematical Expression 11] T(t): The temperature of the steel plate [K] after t seconds following winding. tf: Time in seconds for the steel plate to reach a temperature of 673K. Nx: The total atomic fractions of Si, Mn, and Al in steel. Δt: The measurement interval of T(t) [seconds] (B) A pickling process, comprising a pickling treatment lasting 30 to 200 seconds, wherein the hot-rolled steel sheet is subjected to a pickling process at an average speed of 10 m / min or higher in an environment containing 1.0 to 5.0 mol / L HCl and less than 0.10 mol / L Fe. 3+ It passes through an aqueous solution with a temperature of 70~90℃; (C) Cold rolling process, in which the pickled hot-rolled steel sheet is cold rolled with a reduction rate of 30-75%; (D) A first heat treatment process, which includes heating the obtained cold-rolled steel sheet to a maximum heating temperature of Ac3~950°C, followed by cooling to below 40°C, and satisfying the following conditions (D1) and (D2): (D1) After reaching the aforementioned maximum heating temperature, the dwell time at 600~700℃ is less than 50 seconds, the dwell time at 450~600℃ is less than 500 seconds, and the dwell time at Ms~450℃ is less than 100 seconds. (D2) The average cooling rate between 200℃ and Ms is above 20℃ / second; (E) A second heat treatment process, which includes heating the cold-rolled steel sheet after the first heat treatment to a maximum heating temperature of 80~300°C, and satisfying the following equations (6) and (7): [Mathematical Expression 12] in, [Mathematical Expression 13] t: Time elapsed after reaching 80℃ [seconds] tf: End time of residence at 80~300℃ [seconds] T: Temperature at time t [K] T max Maximum heating temperature [K] (A) Hot rolling process First, a slab having the chemical composition described above associated with the steel sheet is hot-rolled in a hot rolling process, and then the resulting hot-rolled steel sheet is coiled and cooled. This hot rolling process needs to meet the conditions (A1) and (A2) below.
[0070] (A1) When the steel plate temperature is above 1000℃, the cumulative reduction rate between oxide scale removal points is less than 50%; and (A2) The winding temperature is above 400°C and below 650°C, and the cooling satisfies the following formulas (3) to (5).
[0071] [Mathematical Expression 14] in, [Mathematical Expression 15] [Mathematical Expression 16] T(t): The temperature of the steel plate [K] after t seconds following winding. tf: Time in seconds for the steel plate to reach a temperature of 673K. Nx: The total atomic fractions of Si, Mn, and Al in steel. Δt: The measurement interval of T(t) [seconds] The slabs used contain a significant amount of alloying elements, especially the slabs produced by continuous casting, which contain coarse Ti carbides. Therefore, it is necessary to dissolve the alloying elements in the slab, particularly to fully dissolve the Ti. Thus, the slabs are heated before hot rolling, preferably at a temperature of 1200°C or higher. While there is no specific upper limit, excessively high heating temperatures will reduce the yield due to oxide scale removal. Therefore, the heating temperature of the slabs is preferably set below 1300°C. From a manufacturing point of view, the slabs used are preferably cast using continuous casting, but they can also be manufactured using ingot casting or thin slab casting. Furthermore, the slabs exiting the furnace are descaled before rolling begins.
[0072] [(A1) Cumulative reduction rate of oxide scale removal when steel plate temperature is above 1000℃: below 50%] In the hot rolling process, the oxide scale that typically forms on the surface of the steel sheet during this process is removed using a descaling agent such as high-pressure water. In this manufacturing method, descaling is performed multiple times between hot rolling processes, but the cumulative reduction rate of rolling passes performed more than once between adjacent descaling passes (e.g., between the first and second descaling passes, or between the second and third descaling passes) needs to be controlled to be below 50%. When the steel sheet temperature is high, for example, above 1000°C, oxide scale also grows on the steel sheet surface between descaling passes. Therefore, if the steel sheet is forcefully pressed under such conditions, i.e., with a cumulative reduction rate exceeding 50%, the grown oxide scale will be forced into the steel sheet, resulting in a significant unevenness on the steel sheet surface. As a result, on the surface of the final steel sheet, the number density of recesses with a depth exceeding 2 μm and a apex angle of 45 degrees or less exceeds 10.0 per mm, and the hydrogen embrittlement resistance of the bent portions decreases. In this manufacturing method, by controlling the cumulative reduction rate between oxide scale layers when the steel sheet temperature is above 1000°C to below 50%, the indentation of oxide scale into the steel sheet can be suppressed, thereby suppressing the formation of unevenness on the steel sheet surface. Here, the steel sheet temperature is the inlet temperature to the roll. The inlet temperature to the roll can be measured by a thermometer or calculated numerically. As a result, the number density of recesses with a depth exceeding 2 μm and a apex angle of 45 degrees or less on the surface of the final steel sheet can be reduced to below 10.0 per mm. Preferably, the cumulative reduction rate between oxide scale layers is 48% or less. Here, the so-called cumulative reduction rate between oxide scale layers, for example, in the case where the oxide scale removal process includes n rolling passes, is calculated by the following formula. It should be noted that when the steel plate temperature drops below 1000°C during the descaling process, the cumulative reduction rate for rolling passes where the steel plate temperature is above 1000°C from the immediate descaling stage to the roll entry point only needs to be below 50%. Furthermore, if rolling is performed after the final descaling stage, the cumulative reduction rate for rolling passes where the steel plate temperature is also above 1000°C after the final descaling stage must also be below 50%.
[0073] Cumulative reduction rate between oxide scale (%) = (thickness of plate before n rolling passes - thickness of plate after n rolling passes) / thickness of plate before n rolling passes × 100 [(A2) Winding temperature: above 400℃ and below 650℃ and cooling that satisfies equations (3) to (5)] After hot rolling, the resulting hot-rolled steel sheet is coiled at a coiling temperature of more than 400°C and less than 650°C, and then cooled in a manner that satisfies the following formulas (3) to (5).
[0074] [Mathematical Expression 17] in, [Mathematical Expression 18] [Mathematical Expression 19] T(t): The temperature of the steel plate [K] after t seconds following winding. tf: Time in seconds for the steel plate to reach a temperature of 673K. Nx: The total atomic fractions of Si, Mn, and Al in steel. Δt: The measurement interval of T(t) [seconds] If the coiling temperature exceeds 650°C, excessive oxidation occurs on the steel sheet surface, resulting in a surface density of recesses exceeding 2 μm in depth and with a apex angle of 45 degrees or less exceeding 10.0 recesses / mm, thus reducing the hydrogen embrittlement resistance of the bent portions. On the other hand, when the coiling temperature is below 400°C, the hot-rolled steel sheet becomes too hard, leading to a higher rolling load on the mill in the subsequent cold rolling process, which is undesirable. Therefore, in this manufacturing method, the coiling temperature is set to be above 400°C and below 650°C, preferably above 400°C and below 550°C.
[0075] On the other hand, the larger the value of the side in the above formula (3), the more internal oxidation reactions of elements such as Si will occur on the surface of the hot-rolled steel plate.
[0076] Σ in equation (3) above is calculated using a piecewise quadrature method. Δt is a finite value, corresponding to the measurement interval of temperature T(t). For example, it is 100 sec. Do is the diffusion coefficient of oxygen atoms at temperature T(t) [m 2 [ / second], No is the amount of oxygen atoms dissolved in the steel at temperature T(t) (atomic fraction), and Nx is the total amount of the main internally oxidized elements in the steel. Nx can be calculated by converting the mass fraction of each element (Si, Mn and Al) into atomic fractions and summing them up. If it is expressed mathematically, it is shown in the following formula (9).
[0077] [Mathematical Expression 20] Where [X] is the mass fraction of element X, and Mx is the atomic weight of element X. The denominator of the above equation (9) is the sum of all elements added to the target steel.
[0078] Equation (3) above indicates that the greater the diffusion coefficient of oxygen atoms and the greater the amount of oxygen dissolved, the easier the internal oxidation reaction is to proceed. The more elements are oxidized internally, the more difficult it is to proceed. If the internal oxidation reaction proceeds excessively, that is, the value of the side in Equation (3) above is 1.50 or more, the surface roughness of the steel plate after pickling will increase. This roughness is smoothed to some extent by cold rolling, but its effect remains in the final product. As a result, on the surface of the final steel plate, the number density of depressions with a depth of more than 2 μm and a apex angle of less than 45 degrees exceeds 10.0 per mm, and the hydrogen embrittlement resistance of the bent part is reduced.
[0079] On the other hand, when the value of the middle edge in the above equation (3) is less than 0.05, although the surface roughness of the steel plate is improved, the hot-rolled steel plate becomes too hard, and the rolling load of the mill in the subsequent cold rolling process becomes higher, which is not preferred. For example, the slower the cooling, the longer the time tf to reach 673K, and the longer the residence time in the high-temperature region where Do and No are large, so the value of Σ in equation (3) becomes larger, that is, the value of the middle edge in equation (3) becomes larger, and the internal oxidation reaction proceeds more. On the other hand, the faster the cooling, the smaller the value of the middle edge in equation (3), and the more difficult the internal oxidation reaction is to proceed. In addition, No is the amount of oxygen atoms dissolved in the steel at temperature T (t) as mentioned above, and Do is the diffusion coefficient of oxygen atoms. It can also be seen from equations (4) and (5) that the higher the temperature of the steel plate, the larger the values of No and Do become, and the larger the value of Σ in equation (3) becomes. Therefore, for example, a higher coiling temperature leads to a higher steel plate temperature, resulting in a larger value of the middle edge of equation (3), which facilitates internal oxidation. Conversely, a lower steel plate temperature makes internal oxidation more difficult. Thus, by appropriately controlling parameters such as the steel plate temperature and cooling rate during cooling after coiling, the value of the middle edge of equation (3) can be appropriately controlled within a range exceeding 0.05 and below 1.50. Therefore, in this manufacturing method, during the hot rolling process, the coiling temperature is set to exceed 400°C and below 650°C, and the subsequent cooling is controlled in a manner that satisfies equations (3) to (5) above. In particular, the value of the middle edge of equation (3) is controlled to exceed 0.05 and below 1.50, thereby enabling a moderate rolling load in the subsequent cold rolling process and reducing the number density of recesses with a depth exceeding 2 μm and a apex angle of less than 45 degrees on the surface of the final steel plate to less than 10.0 per mm. The value of the middle edge in the above formula (3) is preferably 0.10 or more, more preferably 0.20 or more or 0.30 or more. Similarly, the value of the middle edge in the above formula (3) is preferably 1.00 or less, more preferably 0.70 or less or 0.60 or less.
[0080] [(B) Pickling process] Next, the obtained hot-rolled steel sheet is fed into a pickling process, which includes a pickling treatment for 30 to 200 seconds, wherein the pickling treatment is performed by passing through a solution containing 1.0 to 5.0 mol / L HCl and less than 0.10 mol / L Fe at an average speed of 10 m / min or higher. 3+ In an aqueous solution at a temperature of 70-90°C, pickling is insufficient when the HCl concentration in the pickling solution is below 1.0 mol / L, the aqueous solution temperature is below 70°C, the average speed of the hot-rolled steel sheet is below 10 m / min, or the pickling time is below 30 seconds. This results in uneven removal of the internal oxide layer, including scale and Si oxides. Consequently, the surface of the final steel sheet exhibits a density exceeding 10.0 recesses with a depth greater than 2 μm and a apex angle of less than 45 degrees, and the hydrogen embrittlement resistance of the bent portions decreases. Conversely, when the HCl concentration exceeds 5.0 mol / L, the aqueous solution temperature exceeds 90°C, or the pickling time exceeds 200 seconds, over-pickling occurs, dissolving not only scale and the internal oxide layer into the base metal, resulting in a significant unevenness on the steel sheet surface. Again, the surface of the final steel sheet exhibits a density exceeding 10.0 recesses with a depth greater than 2 μm and a apex angle of less than 45 degrees, and the hydrogen embrittlement resistance of the bent portions also decreases. Furthermore, the Fe in the aqueous solution... 3+ The dissolution of the base metal is promoted by inhibiting the effect of the inhibitor. Relatedly, if Fe in aqueous solution... 3+ When the concentration is above 0.10 mol / L, the dissolution of the base metal becomes significant. As a result, the number density of recesses with a depth exceeding 2 μm and a vertex angle of less than 45 degrees exceeds 10.0 per mm on the surface of the final steel sheet. Therefore, it is important to implement the pickling treatment appropriately, without going over it too much or too little.
[0081] In contrast, in this manufacturing method, a pickling process is performed for 30 to 200 seconds, wherein the pickling process is carried out at an average speed of 10 m / min or higher in an environment containing 1.0 to 5.0 mol / L HCl and less than 0.10 mol / L Fe. 3+ Passing through an aqueous solution at a temperature of 70-90°C can appropriately remove oxide scale and internal oxide layers and suppress over-pickling, thereby inhibiting the formation of unevenness on the steel plate surface. As a result, the number density of depressions with a depth exceeding 2 μm and a vertex angle of less than 45 degrees on the surface of the final steel plate can be reduced to less than 10.0 depressions / mm. Fe in the aqueous solution is preferred. 3+ The content is below 0.06 mol / L, the pickling temperature is 75~85℃, and the pickling time is 50~100 seconds. Fe in aqueous solution 3+ There is no specific lower limit for the content; for example, Fe in aqueous solution. 3+The content can be above 0 mol / L or below 0.001 mol / L. Similarly, there is no particular upper limit to the average speed of hot-rolled steel sheets; for example, the average speed of hot-rolled steel sheets can be below 100 m / min.
[0082] (C) Cold rolling process The hot-rolled steel sheet after pickling is then subjected to cold rolling. To promote recrystallization and smooth the surface of the pickled steel sheet, the reduction rate during cold rolling is set to 30% or more. If the reduction rate is less than 30%, the surface of the steel sheet cannot be sufficiently smoothed, and it is difficult to reduce the number density of recesses with a depth exceeding 2 μm and a apex angle of less than 45 degrees to less than 10.0 per mm on the surface of the final steel sheet. The reduction rate is preferably 40% or more or 50% or more. On the other hand, excessive reduction results in excessive rolling load, leading to an increase in the load on the cold rolling mill. Therefore, the reduction rate is set to 75% or less, preferably 70% or less or 60% or less.
[0083] [(D) First heat treatment process] Next, the obtained cold-rolled steel sheet is heated to a maximum heating temperature of Ac3~950°C in the first heat treatment process, and then cooled to below 40°C. In addition, the first heat treatment process needs to meet the following conditions (D1) and (D2).
[0084] (D1) After reaching the aforementioned maximum heating temperature, the dwell time at 600~700℃ is less than 50 seconds, the dwell time at 450~600℃ is less than 500 seconds, and the dwell time at Ms~450℃ is less than 100 seconds. (D2) The average cooling rate between 200℃ and Ms is above 20℃ / second. [(D1) After reaching the maximum heating temperature of Ac3~950℃, the dwell time at 600~700℃ is less than 50 seconds, the dwell time at 450~600℃ is less than 500 seconds, and the dwell time at Ms~450℃ is less than 100 seconds] To ensure sufficient austenitization and achieve the desired steel microstructure through subsequent cooling, cold-rolled steel sheets need to be heated to a maximum heating temperature of Ac3~950℃. Insufficient austenitization results in a large amount of ferrite formation in the final steel microstructure, sometimes failing to achieve the desired martensite area ratio. Furthermore, after reaching the maximum heating temperature of Ac3~950℃, if the dwell time at 600~700℃ exceeds 50 seconds, or at 450~600℃ exceeds 500 seconds, or at Ms~450℃ exceeds 100 seconds, a greater amount of ferrite and / or bainite is formed, increasing the combined area ratio of ferrite and bainite. Depending on the situation, the martensite area ratio decreases, failing to achieve the desired strength. In this manufacturing method, after reaching the maximum heating temperature of Ac3~950°C, the dwell time at 600~700°C is controlled to be less than 50 seconds, the dwell time at 450~600°C is controlled to be less than 500 seconds, and the dwell time at Ms~450°C is controlled to be less than 100 seconds. This allows the total area ratio of ferrite and bainite to be controlled to be 0~20%, and the area ratio of martensite to be controlled to be 70% or more. Preferably, the dwell time at 600~700°C is less than 30 seconds, the dwell time at 450~600°C is less than 200 seconds, and the dwell time at Ms~450°C is less than 60 seconds. Ac3 (°C) and Ms (°C) can be approximately calculated based on the following formulas (10) and (11). The mass percentage of the element is substituted into the element symbols in the following formulas. For elements not present, 0 mass is substituted.
[0085] Ac3(℃)=912-230.5×C+31.6×Si-20.4×Mn-39.8×Cu-18.1×Ni-14.8×Cr+16.8×Mo+100.0×Al…(10) Ms(℃)=561-474×C-33×Mn-17×Cr-17×Ni-21×Mo-7.5×Si+10×Co…(11) [(D2) Average cooling rate between 200℃ and Ms: ≥ 20℃ / second] By controlling the average cooling rate between 200°C and Ms in the first heat treatment process to 20°C / second or higher, i.e., cooling the cold-rolled steel sheet rapidly between 200°C and Ms, sufficient solid solution of carbon (C) can be ensured in the steel. Therefore, in the subsequent second heat treatment process, this solid solution of C can be fixed in dislocations, significantly reducing the number of hydrogen trapping sites in the steel, and more specifically, significantly reducing the number of dislocations functioning as hydrogen trapping sites. Furthermore, by maintaining an average cooling rate of 20°C / second or higher, the diffusion of C atoms from the already formed martensite to the untransformed austenite during the martensitic transformation is suppressed, inhibiting the formation of locally high-C-concentration austenite regions. The higher the C concentration in austenite, the lower the martensitic transformation temperature; however, the lower the temperature at which the martensite transforms, the more dislocations it contains. By maintaining an average cooling rate of 20°C / second or higher, such low-temperature transformation martensite can be suppressed. Relatedly, when a steel plate is immersed in an aqueous solution of ammonium thiocyanate with a concentration of 100 g / L at 25°C for 48 hours, and then the hydrogen release is measured by heating from room temperature to 300°C at a heating rate of 100°C / h using a temperature desorption analysis method, a steel structure that satisfies the following formula (1) can be formed.
[0086] H 100-200 / H 20-300 <0.30(1) On the other hand, if the average cooling rate between 200°C and Ms is less than 20°C / second, sufficient solid solution of C cannot be ensured in the steel. Therefore, even after the subsequent second heat treatment process, the number of hydrogen trapping sites cannot be sufficiently reduced, and sometimes the steel structure that satisfies the above formula (1) cannot be formed. Preferably, the average cooling rate between 200°C and Ms is 24°C / second or more. In addition to controlling the average cooling rate between 200°C and Ms, the cooling end temperature is also important in order to suppress low-temperature phase transformation martensite. Specifically, the cooling end temperature needs to be set to 40°C or less, preferably 30°C or less. If the cooling end temperature is high, untransformed austenite remains at the end of cooling, which undergoes martensitic phase transformation during cooling after the second heat treatment process, thereby generating a large amount of low-temperature phase transformation martensite containing dislocations with unfixed C, making it difficult to satisfy formula (1).
[0087] [(D) Preferred embodiment of the first heat treatment process] In a preferred embodiment of the first heat treatment process, the atmosphere between Ac1 and Ac3 when the cold-rolled steel sheet is heated to the maximum heating temperature is controlled to satisfy the following formula (8).
[0088] [Mathematical Expression 21] pH2O: Partial pressure of water vapor pH2: partial pressure of hydrogen The log(pH2O / pH2) in the above formula (8) is also called the oxygen potential. The larger this value is, the more decarburization can be carried out on the surface of the steel plate. In this manufacturing method, by controlling the oxygen potential to satisfy the above formula (8), decarburization can be carried out appropriately in such a way that the C concentration on the surface of the steel plate satisfies the above formula (2). As a result, in addition to the effect of a specific combination based on the reduction of hydrogen capture sites and the control of the number density of recesses in the steel plate surface, the hydrogen embrittlement resistance of the bending portion can be further significantly improved. In order to make such an effect more significant, the log(pH2O / pH2) in the above formula (8) is preferably greater than -1.00. More preferably, the log(pH2O / pH2) is -0.90 or more. On the other hand, when the log(pH2O / pH2) is -0.10 or more, sometimes not only decarburization occurs, but also the Fe oxidation of the base metal occurs. Excessive oxidation of the base metal can sometimes have an adverse effect when plating is performed. Therefore, the log(pH2O / pH2) is preferably set to less than -0.10. More preferably, log(pH2O / pH2) is below -0.20 or below -0.30. Ac1 (°C) can be approximately calculated based on the following formula (12). Substitute the mass percentage of the element into the element symbols in the following formula. For elements that are not present, substitute 0 mass%.
[0089] Ac1 (℃)=723-10.7×Mn-16.9×Ni+29.1×Si+16.9×Cr (12) [Platinum coating] When manufacturing coated steel sheets, for example, cold-rolled steel sheets in process (D1), cooling is stopped near the bath temperature (around 460°C in the case of a Zn bath), and the sheets are immersed in the bath. When manufacturing alloyed hot-dip galvanized (GA), reheating and alloying are performed after immersion in the bath. The alloying temperature is in the range of 460~600°C. Alternatively, hot-dip galvanizing (GI) without alloying can also be performed. However, the conditions described in (D1) must be met, including the coating time and alloying time. When manufacturing electroplated zinc (EG), it is performed after cooling to room temperature following (E). These zinc coatings can be performed using any suitable method known to those skilled in the art. Similarly, these zinc coatings can have any composition known to those skilled in the art, including additives such as Al and Mg in addition to Zn. Furthermore, there are no particular limitations on the amount of these zinc coatings applied; they can be the usual amount.
[0090] [(E) Second heat treatment process] The cold-rolled steel sheet after the first heat treatment is heated to a maximum heating temperature of 80~300℃ in the second heat treatment process, and the second heat treatment process needs to satisfy the following formulas (6) and (7).
[0091] [Mathematical Expression 22] in [Mathematical Expression 23] t: Time elapsed after reaching 80℃ [seconds] tf: End time of residence at 80~300℃ [seconds] T: Temperature at time t [K] T max Maximum heating temperature [K] The above (6) and (7) can be understood as indicators of the degree of tempering. Therefore, the larger the value of the side in the above formula (6), the more advanced the tempering is. The inventors have discovered that by appropriately controlling the second heat treatment process, i.e., appropriately tempering the cold-rolled steel sheet, using the above formulas (6) and (7), it is possible to reduce the hydrogen trapping sites in the steel. To explain in more detail, in the previous first heat treatment process, by rapidly cooling between 200°C and Ms, sufficient solid solution of C is ensured in the steel. Then, in the second heat treatment process, by heating to the maximum heating temperature of 80 to 300°C and performing heat treatment (i.e., tempering) in a manner that satisfies the above (6) and (7), the previously ensured solid solution of C can be fixed to the dislocations in the steel. As a result, the hydrogen trapping sites in the steel can be reduced. That is, by first fixing C to the dislocations, the function of dislocations as hydrogen trapping sites can be suppressed. Therefore, by constructing a steel sheet from a steel structure that satisfies the above equation (1), and through a specific combination with the control of the number density of recesses on the surface of the steel sheet as described above, the hydrogen embrittlement resistance of the bent portion in the final steel sheet can be significantly improved. In the second heat treatment process, it is important to properly temper the cold-rolled steel sheet, so that the reduction effect of hydrogen capture sites cannot be achieved if the maximum heating temperature in the second heat treatment process is too high or too low. Similarly, the reduction effect of hydrogen capture sites cannot be achieved if the value of the middle edge in the above equation (6) is too high or too low. Preferably, the maximum heating temperature is 150~250°C, and the value of the middle edge in the above equation (6) is 9000~11100. The interval of t in equation (7) is set to 1 second. If the temperature measurement interval is not 1 second, the data can be straightened to a 1-second interval by linear interpolation.
[0092] The steel sheet manufactured according to the above-described manufacturing method contains Ti and B in amounts of 0.001 to 0.100% by mass and 0.0005 to 0.0050% by mass, respectively, which ensures sufficient solid solution of B, thereby improving hardenability and strengthening the original austenite grain boundaries. Therefore, by combining it with a steel microstructure containing 70% or more martensite by area, high strength of the steel sheet can be achieved, for example, a tensile strength of 1470 MPa or more, and the hydrogen embrittlement resistance of the steel sheet can be improved. Furthermore, by appropriately controlling the hot rolling and pickling processes, the number density of recesses with a depth exceeding 2 μm and a apex angle of less than 45 degrees on the surface of the steel sheet is controlled to less than 10.0 per mm, reducing stress concentration points that may become the starting point for hydrogen embrittlement cracking at the bending points. In addition, by appropriately heat-treating the cold-rolled steel sheet through the first and second heat treatment processes, it is possible to meet the H... 100-200 / H 20-300 By reducing the number of hydrogen trapping sites in the steel to a level <0.30, and through a specific combination of this reduction in hydrogen trapping sites and control over the number density of recesses on the steel sheet surface, the hydrogen embrittlement resistance of the bending section can be significantly improved. Therefore, steel sheets manufactured by the above method are particularly useful in the automotive field, where a high level of strength and hydrogen embrittlement resistance are required.
[0093] The present invention will now be described in more detail by way of examples, but the present invention is not limited to these examples in any way.
[0094] Example In the following embodiments, steel plates according to embodiments of the present invention were manufactured under various conditions, and the tensile strength (TS), uniform elongation (uEL), and resistance to hydrogen embrittlement at the bending portion of the resulting steel plates were investigated.
[0095] First, molten steel is cast using a continuous casting method under the conditions shown in Table 2 to form slabs with various chemical compositions as shown in Table 1. Next, in the hot rolling process, these slabs are heated under the conditions shown in Table 2, followed by hot rolling, and the resulting hot-rolled steel plates are coiled and cooled at the temperatures shown in Table 2. The “maximum cumulative reduction rate between descaling” shown in Table 2 represents the maximum value of the cumulative reduction rate between descaling when the steel plate temperature is above 1000°C during the multiple descaling processes in the hot rolling process (including the cumulative reduction rate after the final descaling if rolling is also performed after the final descaling). In addition, “Equation (3)” in Table 2 represents the value of the middle side of Equation (3) during cooling after coiling based on Equations (3) to (5) above.
[0096] Next, in the pickling process, the hot-rolled steel sheet is passed through 3.0 mol / L HCl and Fe as shown in Table 2 at an average speed of 80 m / min for the time specified in Table 2.3+ Pickling was performed in an aqueous solution of varying concentrations and temperatures, followed by cold rolling at the reduction rates shown in Table 2. The thickness of the cold-rolled sheet was set to 1.4 mm. The resulting cold-rolled steel sheet was heated to the maximum heating temperature shown in Table 2 during the first heat treatment process, and then cooled under the conditions of dwell time within each temperature range shown in Table 2. Next, except for Examples 19 and 20, after plating / alloying treatment was performed at 450–600°C, the cold-rolled or plating steel sheet was cooled between 200°C and Ms at the average cooling rate shown in Table 2, and then cooled to the cooling end temperature shown in Table 2. The atmosphere between Ac1 and Ac3 when the cold-rolled steel sheet was heated to the maximum heating temperature during the first heat treatment process was controlled to the value of log(pH2O / pH2) shown in Table 2.
[0097] Next, the cold-rolled steel sheet after the first heat treatment is heated to the highest heating temperature shown in Table 2 in the second heat treatment process, and finally a second heat treatment is performed based on the above formulas (6) and (7) to obtain a cold-rolled steel sheet or a coated steel sheet. Then, in Example 20, Zn (EG) plating is performed. In Table 2, CR represents the cold-rolled steel sheet without plating, GI represents the steel sheet with hot-dip galvanizing, GA represents the steel sheet with alloyed hot-dip galvanizing, and EG represents the steel sheet with electro-galvanizing.
[0098] The properties of the obtained steel plate were measured and evaluated using the following methods.
[0099] [Tensile strength (TS) and uniform elongation (uEL)] JIS No. 5 test pieces were collected from the direction parallel to the rolling right angle of the steel plate (C direction) along the length of the test piece, and tensile tests were conducted according to JIS Z 2241:2022 to determine the tensile strength (TS) and uniform elongation (uEL).
[0100] [Resistance to hydrogen embrittlement in the bending section] The hydrogen embrittlement resistance of the bent portion was evaluated using a U-bending test. First, a 30mm × 120mm strip test piece 11 was taken from the steel plate, and holes for bolt fastening were machined at both ends of the test piece 11. Then, as... Figure 2As shown, a 180° bend is performed using a punch 12 with a radius of 5 mm. The gap between the punch 12 and the die (support roller) 13 is set to the thickness of the test piece 11 + 1.0 mm. Next, stress is applied to the U-shaped bending test piece 14 after springback by tightening it with bolts 15 and nuts 16. At this time, a GL3 mm strain gauge 17 is attached to the top of the U-shaped bending test piece 14, and stress is applied by controlling the strain. The applied stress is equivalent to 1050 and 1350 MPa. The strain is then converted to stress based on the stress-strain curve previously acquired in the tensile test. Each piece is then immersed in 1000 mL of pH 1.0 hydrochloric acid aqueous solution for 48 hours. The end faces of the U-shaped bending test piece 14 are then milled for finishing. After the test, a crack exceeding 3 mm was confirmed at the top of the bend, which was judged as cracking. Cracks at 1050 MPa were rated as "B", cracks at 1300 MPa but not at 1050 MPa were rated as "A", and cracks at 1300 MPa were not confirmed as "AA".
[0101] Steel plates with a tensile strength of 1470 MPa or higher and a hydrogen embrittlement resistance rating of AA or A are considered high-strength steel plates with excellent hydrogen embrittlement resistance in the bending section. The results are shown in Table 3. In Table 3, "M", "α+B", and "residual γ" represent the area ratios of "martensite", "ferrite and bainite", and "residual austenite", respectively. Additionally, the "number density of recesses" in Table 3 refers to the number density of recesses on the steel plate surface with a depth exceeding 2 μm and a apex angle of less than 45 degrees.
[0102] Referring to Tables 1-3, for Comparative Example 11, the low C content resulted in a decrease in TS (Total Strength). For Comparative Example 12, the high C content led to a decrease in hydrogen embrittlement resistance in the bent portion due to excessive TS. For Comparative Example 13, the high Si content similarly resulted in a decrease in hydrogen embrittlement resistance in the bent portion. For Comparative Example 14, the low Mn content prevented sufficient martensite formation, leading to a decrease in TS. For Comparative Example 15, the high Mn content resulted in excessive martensite formation, resulting in a decrease in hydrogen embrittlement resistance in the bent portion. For Comparative Example 16, the low B content reduced hardenability, leading to a decrease in TS. For Comparative Example 17, the high B content resulted in excessive boride formation in the steel, reducing the hardenability of the steel plate. Consequently, the desired steel microstructure fraction was not obtained, resulting in a decrease in TS. For Comparative Example 18, the absence of Ti prevented the fixation of N as an impurity in the steel as TiN, causing most of the B to precipitate as BN. Consequently, sufficient solid solution of B could not be ensured, reducing hardenability and decreasing TS.
[0103] For Comparative Example 23, it can be considered that during the hot rolling process, the cumulative reduction rate between the descaling layers is high when the steel plate temperature is above 1000°C, thus pressing the descaling layer formed between the descaling layers into the steel plate. As a result, on the surface of the final steel plate, the number density of recesses with a depth exceeding 2 μm and a vertex angle of less than 45 degrees exceeds 10.0 per mm, and the hydrogen embrittlement resistance of the bent portion decreases. For Comparative Example 24, it can be considered that the coiling temperature is high, thus excessive oxidation occurs on the surface of the steel plate. As a result, similarly, on the surface of the final steel plate, the number density of recesses with a depth exceeding 2 μm and a vertex angle of less than 45 degrees exceeds 10.0 per mm, and the hydrogen embrittlement resistance of the bent portion decreases. For Comparative Example 25, it can be considered that the cooling after coiling does not satisfy the above formula (3), that is, the value of the middle edge in the above formula (3) is 1.50 or higher, the internal oxidation reaction is excessive, and the unevenness of the steel plate surface increases after pickling. As a result, similarly, on the surface of the final steel sheet, the number density of recesses with a depth exceeding 2 μm and a vertex angle of less than 45 degrees exceeds 10.0 per mm, and the hydrogen embrittlement resistance of the bent portions decreases. For Comparative Example 26, it can be considered that during the pickling process, the Fe in the aqueous solution... 3+ The high content of the base metal significantly leads to its dissolution. As a result, the number density of recesses with a depth exceeding 2 μm and a apex angle of less than 45 degrees exceeds 10.0 per mm on the surface of the final steel sheet, resulting in reduced hydrogen embrittlement resistance in the bent portions. For Comparative Example 27, it can be assumed that the pickling time was short, resulting in insufficient pickling and uneven removal of the internal oxide layer, including oxide scale and Si oxides. As a result, the number density of recesses with a depth exceeding 2 μm and a apex angle of less than 45 degrees exceeds 10.0 per mm on the surface of the final steel sheet, resulting in reduced hydrogen embrittlement resistance in the bent portions. For Comparative Example 28, it can be assumed that the temperature of the aqueous solution in the pickling process was low, resulting in insufficient pickling and uneven removal of the internal oxide layer, including oxide scale and Si oxides. As a result, the number density of recesses with a depth exceeding 2 μm and a apex angle of less than 45 degrees exceeds 10.0 per mm on the surface of the final steel sheet, resulting in reduced hydrogen embrittlement resistance in the bent portions. For Comparative Example 29, it can be assumed that the temperature of the aqueous solution in the pickling process was high, resulting in over-pickling and dissolution of the base metal in addition to the oxide scale and internal oxide layer. As a result, the number density of recesses with a depth exceeding 2 μm and a vertex angle of less than 45 degrees on the surface of the final steel sheet exceeded 10.0 per mm, and the hydrogen embrittlement resistance of the bent portion decreased. For Comparative Example 30, the reduction rate in the cold rolling process was low, so the surface unevenness of the steel sheet could not be sufficiently smoothed. Similarly, the number density of recesses with a depth exceeding 2 μm and a vertex angle of less than 45 degrees on the surface of the final steel sheet exceeded 10.0 per mm, and the hydrogen embrittlement resistance of the bent portion decreased.
[0104] For Comparative Example 31, the highest heating temperature in the first heat treatment process was low, resulting in insufficient austenitization and the formation of a large amount of ferrite in the final steel microstructure, failing to achieve the desired martensite area ratio. Consequently, the TS (steel strength) decreased. For Comparative Example 33, the dwell time at 600–700°C in the first heat treatment process was long, leading to a higher combined area ratio of ferrite and bainite, and thus a decrease in TS. For Comparative Example 34, the dwell time at 450–600°C in the first heat treatment process was long, resulting in a higher combined area ratio of ferrite and bainite, which, consequently, prevented the achievement of the desired martensite area ratio. Consequently, TS decreased. For Comparative Example 35, the dwell time at Ms–450°C in the first heat treatment process was long, resulting in a higher combined area ratio of ferrite and bainite, which, consequently, prevented the achievement of the desired martensite area ratio. Consequently, TS decreased. For Comparative Example 36, it can be considered that the average cooling rate between 200°C and Ms in the first heat treatment process is slow, so it is not possible to sufficiently ensure the solidification of C in the steel, and even after the subsequent second heat treatment process, the number of hydrogen trapping sites cannot be sufficiently reduced. As a result, a steel structure that satisfies the above formula (1) cannot be formed, and the hydrogen embrittlement resistance of the bending portion is reduced. For Comparative Example 37, it can be considered that the cooling end temperature in the first heat treatment process is high, so a large amount of low-temperature phase transformation martensite containing dislocations with unfixed C is generated in the final steel structure. As a result, a steel structure that satisfies the above formula (1) cannot be formed, and the hydrogen embrittlement resistance of the bending portion is reduced. For Comparative Example 38, it can be considered that the maximum heating temperature in the second heat treatment process is low, so it is not possible to sufficiently fix the solidified C in the dislocations in the steel, and the number of hydrogen trapping sites cannot be sufficiently reduced. As a result, a steel structure that satisfies the above formula (1) cannot be formed, and the hydrogen embrittlement resistance of the bending portion is reduced. For Comparative Example 39, it can be considered that the highest heating temperature in the second heat treatment process is high, and it does not satisfy the above formula (6). Therefore, the C solution cannot be properly fixed to the dislocations in the steel, and the number of hydrogen embrittlement sites cannot be sufficiently reduced. As a result, a steel structure that satisfies the above formula (1) cannot be formed, and the hydrogen embrittlement resistance of the bent portion is reduced. For Comparative Example 40, it can be considered that the above formula (6) is not satisfied in the second heat treatment process. Therefore, the C solution cannot be properly fixed to the dislocations in the steel, and the number of hydrogen embrittlement sites cannot be sufficiently reduced. As a result, a steel structure that satisfies the above formula (1) cannot be formed, and the hydrogen embrittlement resistance of the bent portion is reduced.
[0105] In contrast, the steel plates in all embodiments have a specified chemical composition, and by appropriately controlling the conditions in the manufacturing process, the steel microstructure can be configured to contain martensite of 70% or more, a total of ferrite and bainite of 0-20%, and retained austenite of 0-10% by area, thereby achieving a high strength of 1470 MPa or more. Furthermore, by controlling the number density of recesses with a depth exceeding 2 μm and a apex angle of 45 degrees or less on the surface of the steel plate to 10.0 per mm or less, stress concentration points that may become the starting point of hydrogen embrittlement cracking in the bending section can be reduced, thereby satisfying H 100-200 / H 20-300 A specific combination of reduced hydrogen trapping sites (<0.30) significantly improves the hydrogen embrittlement resistance of the bend.
[0106] In particular, the surface layer of the steel plate is properly decarburized. Therefore, for Examples 1-10, 19-21, and 41, which satisfy the above formula (2) and control the number density of recesses with a depth of more than 2 μm and a apex angle of less than 45 degrees on the surface of the steel plate to less than 5.0 per mm, the hydrogen embrittlement resistance of the bending portion is evaluated as AA. Compared with Example 32, which does not satisfy formula (2) (the hydrogen embrittlement resistance of the bending portion is evaluated as A), the hydrogen embrittlement resistance is further improved. In addition, Examples 1-7, 9, 10, 21, 22, 32, and 41, which have a steel structure consisting of more than 2% ferrite and bainite and more than 1% retained austenite by area, achieve a uniform elongation of more than 5.0%.
[0107] Explanation of reference numerals in the attached figures 1: Steel plate 2: concave part SH: Surface height CL: Centerline D: Depth θ: Vertex angle 11: Long strip test piece 12: Punch 13: Stamping Die 14: U-bending test piece 15: Bolts 16: Nut 17: Strain gauge
Claims
1. A steel plate, characterized in that, It has the following chemical composition: by mass%, C:0.16~0.35%、 Si: 0.001~0.80% Mn: 1.00~3.50%, P: below 0.050% S: Below 0.0100% Al:0.001~1.000%、 Ti: 0.001~0.100% B:0.0005~0.0050%、 N: below 0.0100% O: Below 0.0100% Cr:0~1.00%、 Mo: 0~1.00% Cu: 0~1.00%, Ni: 0~1.00% Co: 0~1.00%, W:0~1.00%、 Ta: 0~1.000% Sn: 0~1.00% Sb: 0~0.50%, Nb: 0~0.200% V:0~1.00%、 As: 0~0.100% Zn: 0~1.000%, Ca: 0~0.0100% Mg: 0~0.0100% Zr:0~0.0100%、 Hf: 0~0.0100% Bi: 0~0.0100% REM: 0~0.0100%, and The remaining portion consists of Fe and impurities. The steel microstructure at a location 1 / 4 thickness from the surface contains, by area %: Martensite: over 70% The total amount of ferrite and bainite: 0~20%, and Residual austenite: 0~10%, The number density of recesses on the surface with a depth exceeding 2 μm and a vertex angle of less than 45 degrees is less than 10.0 per mm, and When the hydrogen release is determined by immersing the sample in an aqueous solution of 100 g / L ammonium thiocyanate at 25 °C for 48 hours, followed by heating from room temperature to 300 °C at a heating rate of 100 °C / h using a temperature desorption analysis method, the following equation (1) is satisfied. H 100-200 / H 20-300 <0.30(1) H 100-200 Hydrogen emission at 100~200℃ (mass ppm) H 20-300 Hydrogen emission at 20~300℃ (mass ppm).
2. The steel plate according to claim 1, characterized in that, When the C concentration is measured from the surface of the steel plate along the depth direction using a high-frequency glow discharge emission spectroscopy (GDS) device, the following equation (2) is satisfied. [Mathematical Expression 1] C b C content (mass%) of steel plate C n C concentration (mass%) at the nth measurement point x n : Depth of the nth measurement point (μm) x n-1 : Depth of the (n-1)th measurement point (μm) l: n when the depth of the measurement point reaches 5μm or more m: n when the depth of the measurement point reaches 30μm or more.
3. The steel plate according to claim 1 or 2, characterized in that, The steel microstructure at a location 1 / 4 thickness from the surface contains, by area %: The total amount of ferrite and bainite: 2~20%, and Residual austenite: 1~10%.
4. The steel plate according to claim 1 or 2, characterized in that, Its tensile strength is above 1470MPa.
5. The steel plate according to claim 1 or 2, characterized in that, It has a hot-dip galvanized layer or an alloyed hot-dip galvanized layer on at least one surface.
6. A component, characterized in that, It comprises the steel plate as described in claim 1 or 2.
7. The method for manufacturing the steel plate according to claim 1 or 2, characterized in that, It includes the following processes: (A) A hot rolling process comprising hot rolling a slab having the chemical composition of claim 1, followed by coiling and cooling the resulting hot-rolled steel sheet, and satisfying the following conditions (A1) and (A2): (A1) When the steel plate temperature is above 1000℃, the cumulative reduction rate between oxide scale removal points is less than 50%, and (A2) The winding temperature is above 400°C and below 650°C and the cooling satisfies the following formulas (3) to (5). [Mathematical Expression 2] in, [Mathematical Expression 3] [Mathematical Expression 4] T(t): The temperature of the steel plate [K] after t seconds following winding. tf: Time in seconds for the steel plate to reach a temperature of 673K. Nx: The total atomic fractions of Si, Mn, and Al in steel. Δt: The measurement interval of T(t) [seconds]; (B) A pickling process, comprising a pickling treatment lasting 30 to 200 seconds, wherein the hot-rolled steel sheet is subjected to a pickling process at an average speed of 10 m / min or higher in an environment containing 1.0 to 5.0 mol / L HCl and less than 0.10 mol / L Fe. 3+ It passes through an aqueous solution with a temperature of 70~90℃; (C) Cold rolling process, in which the pickled hot-rolled steel sheet is cold rolled with a reduction rate of 30-75%; (D) A first heat treatment process, comprising heating the obtained cold-rolled steel sheet to a maximum heating temperature of Ac3~950°C, followed by cooling to below 40°C, and satisfying the following conditions (D1) and (D2): (D1) After reaching the maximum heating temperature, the residence time at 600~700°C is less than 50 seconds, the residence time at 450~600°C is less than 500 seconds, and the residence time at Ms~450°C is less than 100 seconds. (D2) The average cooling rate between 200℃ and Ms is above 20℃ / second; (E) A second heat treatment process, which includes heating the cold-rolled steel sheet after the first heat treatment to a maximum heating temperature of 80~300°C, and satisfying the following equations (6) and (7): [Mathematical Expression 5] in, [Mathematical Expression 6] t: Time elapsed after reaching 80℃ [seconds] tf: End time of residence at 80~300℃ [seconds] T: Temperature at time t [K] T max Maximum heating temperature [K].
8. The method according to claim 7, characterized in that, In the first heat treatment process, the atmosphere between Ac1 and Ac3 when the cold-rolled steel sheet is heated to the highest heating temperature satisfies the following formula (8). [Mathematical Expression 7] pH2O: Partial pressure of water vapor pH2: Partial pressure of hydrogen.
Citation Information
Patent Citations
High-strength cold-rolled steel sheet and manufacturing method therefor
WO2019181950A1
Galvanized steel sheet and production method therefor
WO2019212047A1